2000
DOI: 10.1046/j.1365-2427.2000.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and assemblage structure of Trichoptera in Danish streams

Abstract: Summary Species richness and assemblages of Trichoptera from 157 ‘pristine’ Danish lowland stream sites were analyzed, for dependence on geographical position of the sites and simple physical variables, using two way indicator species analysis and detrended correspondence analysis. A total of 106 species were recorded, representing ≈ 90% of the species pool known from Danish streams. Only seven species occurred at more than half the sites, whereas an additional 11 species were found at more than a quarter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
3
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 41 publications
4
55
3
2
Order By: Relevance
“…stream width, discharge, stream order) and benthic macroinvertebrate species richness seems to be a general pattern in European streams of the first to fifth order (cf. Wiberg-Larsen et al, 2000). In our study, diversity of caddisflies was higher in the upper part of the Hron River than in the lower stretches.…”
Section: > River Zonationsupporting
confidence: 40%
See 2 more Smart Citations
“…stream width, discharge, stream order) and benthic macroinvertebrate species richness seems to be a general pattern in European streams of the first to fifth order (cf. Wiberg-Larsen et al, 2000). In our study, diversity of caddisflies was higher in the upper part of the Hron River than in the lower stretches.…”
Section: > River Zonationsupporting
confidence: 40%
“…Several studies demonstrated strong influence of stream size on macroinvertebrate diversity -low species richness in spring areas and its increase in the downstream direction (e.g. Wiberg-Larsen et al, 2000;Heino et al, 2005). The same diversity pattern was observed in mayfly assemblages of upstream tributaries of the Hron River (Svitok, 2006) but not in caddisfly assemblages of the same sites (Novikmec, 2005).…”
Section: > River Zonationmentioning
confidence: 75%
See 1 more Smart Citation
“…Trichoptera larvae are found in a wide variety of aquatic environments from fast flowing open channels to lentic bodies and ephemeral pools (Bacher and Waringer 1996;Wiberg-Larsen et al 2000). In order to interpret the past environmental history, it is necessary to employ an analogue approach through direct comparison with the modern fauna, an approach that is generally considered valid for the latter half of the Holocene (Lowe and Walker 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This spatial heterogeneity strongly influences the distribution of stream-dwelling organisms (Allan 1995). Studies conducted at the reach scale (linear spatial scale: several tens of metres, Giller & Malmqvist 1998) showed that stream order (Strahler 1952) had a broad capability of predicting the structural and/or functional properties of macroinvertebrate communities (Vinson & Hawkins 1998), including caddisflies (Wiberg-Larsen et al 2000, Céréghi-no et al 2003. Beside stream order, environmental heterogeneity may strongly influence the assemblage characteristics of macroinvertebrate communities at the mesohabitat scale (i.e., a few metres, Vinson & Hawkins 1998, Bournaund et al 1998, Beisel et al 1998, 2000Usseglio-Polatera et al 1999).…”
Section: Introductionmentioning
confidence: 99%